A Review of Analytical Approaches to Understanding the Drivers of Illicit Trade Agglomeration - Krylova, Yulia (International Journal of Criminology and Sociology, 2026)
Illicit trade hubs pose a significant challenge to global economies, undermining legitimate markets and fueling a range of criminal activities. Despite growing scholarly attention to illicit trade, limited research has examined the underlying conditions that enable illicit trade activities to agglomerate in particular hubs. This article reviews major analytical approaches relevant to understanding illicit trade agglomeration, drawing on insights from criminology, political economy, and economic geography. It argues that illicit trade agglomeration is driven by the interaction of three interconnected dimensions: political and institutional vulnerabilities, socioeconomic conditions, and infrastructure-related enabling environments. The interaction between these dimensions forms an ecosystem that facilitates illicit trade agglomeration and contributes to the emergence and persistence of illicit trade hubs. By conceptualizing illicit trade hubs as multidimensional ecosystems rather than isolated criminal hotspots, the review contributes to interdisciplinary debates on transnational crime, governance, and the spatial concentration of illicit economies.